2014
DOI: 10.1016/j.jtcvs.2013.10.077
|View full text |Cite
|
Sign up to set email alerts
|

Surgical palliation in patients with a single ventricle and dextrocardia

Abstract: Surgical outcomes of single-ventricle palliation seem poor in patients with dextrocardia. Aggressive management of congenital AVVR might improve the long-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, in contrast to published data, the mortality of patients undergoing TCPC was lower, but was not significantly different compared to children without DS.Poh et al. (2014) 17 AustraliaRoyal Children's Hospital, Melbourne1990–2008The medical data of 41 consecutive patients with single-ventricle physiology and dextrocardia in a single institution were investigated. In this cohort, 19 patients had heterotaxy syndrome.Twenty-five of the 41 patients had atrioventricular valve regurgitation (AVVR) on presentation (mild, 13; moderate, 9; severe, 3).The surgical outcomes of single ventricular palliation were less optimal in patients with dextrocardia.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…However, in contrast to published data, the mortality of patients undergoing TCPC was lower, but was not significantly different compared to children without DS.Poh et al. (2014) 17 AustraliaRoyal Children's Hospital, Melbourne1990–2008The medical data of 41 consecutive patients with single-ventricle physiology and dextrocardia in a single institution were investigated. In this cohort, 19 patients had heterotaxy syndrome.Twenty-five of the 41 patients had atrioventricular valve regurgitation (AVVR) on presentation (mild, 13; moderate, 9; severe, 3).The surgical outcomes of single ventricular palliation were less optimal in patients with dextrocardia.…”
Section: Resultsmentioning
confidence: 87%
“…Outcome of univentricular repair in patients with Down's syndrome (Furukawa et al., 2013) 16 Surgical palliation in patients with a single ventricle and dextrocardia (Poh et al., 2014) 17 High-risk single ventricle palliation in children with Down's syndrome: single institution experience (Ooi et al., 2015) 18 …”
Section: Methodsmentioning
confidence: 99%
“…However, according to a single institution study of patients with single-ventricle physiology and dextrocardia reported in 2014 by Chin L et al, only 56% of patients aged 15 years or younger with this condition survived, and the surgical outcome was poor. 10 Therefore, we consider that effective CPR for these patients is still important in emergency medicine. Recently, precision medicine has been emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, the chest compression point recommended in current guidelines was the same for all cardiac arrest patients regardless of cardiac anomaly, including Fontan circulation patients with dextrocardia [7,8]. 7,8 In a recent study based on CT (Computed Tomography) analysis, researchers reported that the optimal compression point in patients with Fontan circulation undergoing CPR was approximately 5-25% of the lower sternum, which was lower than suggested in the current guidelines [9], however patients with dextrocardia, de ned as cardiac positioning with a rightward base-apex axis, [10,11] were not considered in the study. [9][10][11] Additionally, there have been no related studies on compression points in patients with dextrocardia.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality rates were 58% in isomerism and 27% in the non-isomerism groups. 18 In our study, we identified 12 out of 64 patients as Dextrocardia without isomerism (SSD). All SSD patients underwent single ventricle repair, and the mortality rate was 41% (5 out of 12).…”
Section: Discussionmentioning
confidence: 99%